Minor arts and regional styles in East Greece, 700-500 B.C - Spier, J; Spier, Jeffrey B. (1988)
﻿ This study attempts to establish a body of material that can be attributed to East Greek workshops in the Archaic period. All bronze work, ivory and wood carving, jewelry and works in precious metal, rings, engraved gems, and coins are categorized and discussed. A corpus of all these materials is intended, with the exception of coins, where only an outline for future work is suggested. Special attention is given to findsites, contexts, and chronological problems. Individual workshops for the various minor arts are identified, and their stylistic traits and development is discussed. In the seventh century, East Greek bronzework, ivories, and even iconography were dependent especially on the more advanced Mainland Greek schools as well as on Oriental models, but during the sixth century several distinctively Ionian stylizations and sculptural types were developed. Other minor arts, notably the jewelry in Ionia, were more innovative and appear to have been created late in the seventh century, perhaps under Lydian patronage. Gem engraving was a relatively late (mid-sixth century) orientalizing art that was quickly developed in East Greek schools, although they are difficult to localize. The extent of an East Greek koine style is also examined. In many cases, a common style is not shared by different media, but some distinctive stylizations, especially those based on sculptural prototypes in the sixth century, can occur in a range of minor arts.